The Management of Heavy Menstrual Bleeding After Percutaneous Coronary Intervention in a Woman of Reproductive Age - Zhi-Chun Gu; Fang-Hong Shi; Jie Zhu; Fang Wan; Long Shen; Hao Li (Frontiers Media S.A., 2019)
Heavy menstrual bleeding (HMB), previously known as menorrhagia, is in place with heavy flow and longer lasting days of bleeding during menstrual period, sequentially leading to anemia. We reported a rare case of HMB in a 33-year-old patient after percutaneous coronary intervention (PCI), who presented with acute coronary syndromes (ACS), uremia and systemic lupus erythematosus before PCI. This patient received three times of hemodialysis weekly (Monday, Wednesday, and Friday). On the next day after PCI, this patient began to have menstruation. On the fifth day of menstruation, the patient complained of HMB and physical discomfort, with an urgent need for consultation of gynecologist. After gynecologist consultation, this patient was under oxytocin treatment. However, 2 days of oxytocin treatment did not significantly improve HMB. Afterward, the menstrual volume of patients was significantly reduced on eighth day of menstruation after once therapy of testosterone propionate and norethindrone. Regarding the reasons of HMB, heparin in hemodialysis and antiplatelet drugs utilized (aspirin and clopidogrel) after PCI may be contributors to the HMB. In addition, uterine myoma, cervical canal cyst, renal insufficiency and CYP2C19∗2 heterozygous are also possible contributors to HMB. There is no such case of whom had HMB in reproductive age with ACS, uremia and systemic lupus erythematosus under hemodialysis and antiplatelet therapy. More clinical safety data on HMB of reproductive age women who are under antithrombotic therapy are required.